ChemInform Abstract: Kinetic Resolution of Propargylamines via a Highly Enantioselective Non‐enzymatic N‐Acylation Process. Issue 9 (5th March 2013) - Kolleth, Amandine; Christoph, Sarah; Arseniyadis, Stellios; Cossy, Janine
Abstract A variety of acetamides (III) is obtained by a highly enantioselective acetyl transfer from acylating agent (II) to amines (I).